Physicochemical indicators and sensory quality analysis of kiwi wines fermented with different Saccharomyces cerevisiae. Issue 11 (16th September 2022) - Chen, Xuexue; Peng, Mengdi; Wu, Dianhui; Cai, Guolin; Yang, Hua; Lu, Jian
Abstract: In this study, the physicochemical indicators including total phenols, in vitro antioxidant activity, organic acids, monomeric phenols, free amino acids, and flavor compounds of kiwi wines fermented by 5 yeasts were determined, and sensory evaluation of 5 kiwi wines was carried out. A total of 104 flavor compounds were identified in 5 wines, of which borneol was reported in kiwi wines for the first time. The kiwi wine fermented by Saccharomyces cerevisiae XX‐16 had a characteristic of rich varieties and high content of terpenes and low content of alcohols. XX‐16 also showed the best fermentation ability, the total phenolic content, in vitro antioxidant activity, and sensory evaluation of kiwi wine fermented by XX‐16 were excellent. All the results showed that S. cerevisiae XX‐16 had the application potential for brewing high quality kiwi wine. Novelty impact statement: Esters and terpenes were important compounds that determined the aroma quality of kiwi wine. The kiwi wine fermented by XX‐16 had the highest in vitro antioxidant activity. XX‐16 was the most suitable yeast for brewing kiwi wine.